A LÍNGUA NO MUSEU E NO DOCUMENTÁRIO “A CHAMA DA LÍNGUA”: FUNCIONAMENTOS DA CONTRADIÇÃO, DAS ALTERIDADES E DAS DIFERENÇAS - Schon, Suhaila Mehanna (2018)
In this investigation, we made the reading of the urban space Museum of the Portuguese Language, with a cut in the space / place in which the file is structured from the language and not of an event or name to be remembered / celebrated. The Museum, which has an interactive section, is closed due to the fire that occurred in late 2015 and, because of the language, it differs from the traditional museums. The difference stems mainly from the fact that museums 'hold' memories and are meant as spaces that accumulate documents and memorable objects, making memory and oblivion and celebration work at the same time and place. The Language Museum, through the textualities of literature, grammar, daily life and the media highlights language peculiarities. The theoretical foundations are those of Discourse Analysis (AD), a discipline of intermedium, because it works in the contradiction between psychoanalysis, Marxism and linguistics, according to Pêcheux (2009), Orlandi (2012, 2015), and isn’t fourth trend of Linguistics. In this perspective, developed by Pêcheux in France, from 1969 and by Orlandi (19882001-2003-2012-2013-2015), in Brazil, we also think of the Museum in the subject / society / ideology relationship, articulating different domains, which signal to the individuation of the subject. This relation, according to the theory studied, is sustained on the one hand, in the subject as being always the center, because without it there is no discourse and no effects of meanings and, on the other hand, in the subject always ideological and affiliated with formations discursive, which determine the language he speaks and the language that means it. Other analysts that constitute our theoretical framework are: Venturini (2009, 2016, 2017), Silva Sobrinho (2011), Cervo (2012) and Romão (2010 and 2017). The question of research, which we seek to answer with this investigation is: What imaginaries support the museum / language relationship from the perspective of researchers and the testimonies circumscribed to the sphere of documentary, post-fire? This question raises another question, more punctual, namely: What functions have supported the Museum of Language, as a space that had the language - as an object of exposure, when contradictorily the language is not object, but ideological functioning, which results from a marked construction by history, by ideology and by the politics of knowledge about the subject and of social formation? In order to answer them, we consider the founding theory quoted and the conception of language at work by the real of the language and by the real of history. In addition, we have taken up new technologies such as grammar and dictionaries that allow us to put in suspense the concept of language that supports / legitimates the testimonies about the language in the Museum and the effect of the 'flame' in the documentary "The Flame of Language”, so that the language of life resounds in spite of the ashes, as a metaphor of the language that remains, despite the fire that destroyed what was in the Museum, signaling to the language as an immaterial patrimony, in which memories and discourses function through which is visible, letting you glimpse the muted / erased. The clippings are the testimonies of researchers about the language in the Museum and about the text-image "flame", with which the documentary closes.